2016
DOI: 10.3389/fpsyg.2016.01928
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Internalizing Problems in 6–8 Year Old Children: A Universal School-Based Program

Abstract: The Aussie Optimism Program: Feelings and Friends (AOP-FF) is a 10 week, universal mental health promotion program based on social/emotional and cognitive and behavioral strategies. The aim of the current study was to evaluate the efficacy of a universal Cognitive Behavioral Therapy based program in preventing and reducing internalizing problems in 6–8 year olds (Years 1–3 in Australia). Year 1–3 students from a low SES primary school (N = 206) were randomly assigned in classes to either an intervention or a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 83 publications
3
23
1
Order By: Relevance
“…This differs from findings of prior trials of this program (Pophillat, 2007; Green, 2008) and other prevention programs (e.g., Hudson et al, 2009) that have found significant reductions in parent-reported anxiety. An interesting finding from the current research was the significant intervention effect for parent-report symptoms of separation anxiety disorder (SAD).…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…This differs from findings of prior trials of this program (Pophillat, 2007; Green, 2008) and other prevention programs (e.g., Hudson et al, 2009) that have found significant reductions in parent-reported anxiety. An interesting finding from the current research was the significant intervention effect for parent-report symptoms of separation anxiety disorder (SAD).…”
Section: Discussioncontrasting
confidence: 94%
“…These results are similar to prior clinical trials, which have failed to find significant reductions in child-reported symptomology using clinical measures (e.g., Pophillat, 2007; Green, 2008; Fresel, 2013). In fact, numerous trials of prevention programs for children have failed to find post-test reductions in child-reported depressive and anxious symptoms (e.g., Dadds et al, 1997; Lock and Barrett, 2003; Hudson et al, 2009).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…To date, only a small number of studies have aimed to prevent both anxiety and depression in children simultaneously (e.g., Ehrenreich‐May & Bilek, 2011; Lowry‐Webster et al, 2001; Pophillat et al, 2016). A meta‐analysis conducted by Johnstone et al (2018) found that these studies tend to show small effects for reducing and preventing depressive symptoms; however, there is less consistency regarding the reduction in anxiety symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Many universal prevention programs focus on building emotional resilience (e.g., Lowry‐Webster, Barrett, & Dadds, 2001; Pophillat et al, 2016), which has been shown to be a protective factor against the development of depression and anxiety (Moore & Woodcock, 2017), and to be related to increased wellbeing in youth (Panter‐Brick & Leckman, 2013). Indeed, several school‐based intervention programs that focus on developing resilience have been shown to reduce symptoms of anxiety and depression in clinical child samples (Baum et al, 2013; Tol et al, 2014), and substance use and violent behavior in adolescents (Griffin, Holliday, Frazier, & Braithwaite, 2009).…”
Section: Introductionmentioning
confidence: 99%